Is This How I Will Be Treated? Reducing Uncertainty through Recruitment Interactions - Walker, H. Jack; Bauer, Talya N.; Cole, Michael S.; Bernerth, Jeremy B.; Feild, Hubert S.; Short, Jeremy C. (Academy of Management Journal, 2013)
While a great deal of research has investigated strategies for increasing job seekers' initial attraction to organizations, far less is known about how job seekers respond to recruitment activities after application submission. We draw from signaling, uncertainty reduction, and uncertainty management theories to develop a conceptual model of the relationship between recruitment interactions (contact episodes) after application submission and organizational attraction. We test this model in three independent studies with data collected at multiple time periods. Study 1 employed a time-lagged research design with actual job seekers. Findings showed that justice perceptions associated with recruitment interactions influence attraction to an organization indirectly and directly via positive relational certainty (i.e., reduced uncertainty regarding how organizational relations might be upon entering the organization). Study 2 used a controlled experimental design to provide additional evidence of the relational certainty mechanism through which justice signals influence attraction. Finally, Study 3 incorporated a longitudinal (repeated-measures) design to examine reactions to recruitment interactions over ten weeks. Results indicated that the relationship between justice signals and organizational attraction via positive relational certainty is dynamic, suggesting that organizations should carefully manage their communications throughout the recruitment process.